Wifi Network Security Analysis Using Scanning Signal Method In Excellent School Pearl Of The Mother Of Bengkulu City - Alamta, Fahmi; Aspriyono , Hari; Rohmawan , Eko Prasetyo (CV. Generasi Insan Rafflesia, 2022)
The purpose of this study is to analyze the security of the WiFi network in Mutiara Bunda extraordinary school, in order to determine the level of security, analyze the network speed. and add network security using mikrotik using Firewall and WiFi hotspot features. The research method used is the Signal Scanning method, namely moving activities in a certain area, mapping Access Point for statistical purposes. The author conducts a network security analysis using two stages of testing, the first stage is to do a login test, try to break into WiFi using the Dummper application, then to analyze the signal strength using the InSSIDer and Vistumbler applications, and use the K-Mac application to test the security of the network, The author also draws conclusions, and adds network security, namely the firewall and WiFi hotspot features using Mikrotik, then the author performs the second testing phase, the stages are the same as the first testing phase,and draws conclusions. The advice from the author is for the agency to be able to maintain and always update network security, so that it can run and be maintained properly